Total Quality Management dan Strategi Reformasi di Sektor Publik - Agus Pramusinto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1998)
This essay discusses Total Quality Management which has been a prominent issue in enhancing quality of products and services. TQM which was firstly applied in the private sectors is in fact not the only idea of quality management. Some practicioneï€´s of management such as Frederick Taylor and Elton Mayo were also concerned with ideas similar with that of W. Edward Denting. There are some debates in relations to the application of TQM in the Public Sector. In this essay, the author shows that TQM has travelled to diffirent countries which in font unavoidably adopts different cultures. Therefore, it would be possible to transplant TQM from the private sector and adopt it in the Public Sector. TQM is compatible with the notion of administrative reform directed toward achieving efficiency, effectiveness and human resource development. Looking at the Malaysian experience in implementing TQM, it seems that the success of quality management is due to the management commitment coming from the top spreading at every level of bureaucracy.